Data Analysis of Social Media’s Impact on COVID19 Pandemic Users’ Mental Health - Deshinta Arrova Dewi (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2022)
Social media has a significant impact on people's daily lives and spread widely. Unrestrained usage of social media could have worsening consequences on mental health. The majority of COVID-19 users who were exposed to social media learned about numerous facts, which made their anxiety and depression-related mental health disorders worse. This study aims to determine how social media usage affects users' mental health during the COVID19 pandemic. Through surveys and expert interviews, this study collects both quantitative and qualitative data. Total number of respondent involved was 106 with average age group of 18-41 year old. Using reliability testing (Cronbach alpha test) and inferential statistic (Pearson Correlation and Chi Square), results show that during the COVID-19 pandemic, there is a significant link between social media use and mental health. Anxiety and depression brought on by social media are common among young adults, predominantly female, between the ages of 18 and 24, than in men. Additionally, correlation plot analysis with variety of queries reveal the mental health issues and activities on social media.